Autologous seminal plasma and post-breeding uterine lavage as alternative options to improve fertility rates of jennies inseminated with cryopreserved jack semen - Oliveira, P.V.L.F. [UNESP]; Segabinazzi, L.G.T.M. [UNESP]; Crespilho, A.M. [UNESP]; Oliveira, J.V.; Silva, A.C. [UNESP]; Freitas-Dell’Aqua, C.P. [UNESP]; Dell’Aqua, J.A. [UNESP]; Papa, F.O. [UNESP] (Elsevier, 2025)
BACKGROUND: Poor fertility of cryopreserved semen remains a challenge in donkeys. AIMS/OBJECTIVES: This study evaluated strategies to enhance fertility of cryopreserved semen in donkeys. METHODS: Experiment 1 assessed in vitro parameters of semen cryopreserved with two freezing-semen protocols (BC and mINRA). For evaluation, samples were thawed and split into two aliquots: one served as a control, and the second was re-extended with seminal plasma (SP). Sperm motility, plasma membrane and acrosome integrity (PMAI), lipid peroxidation (LPO), and hydrogen peroxide (H₂O₂) were analyzed. Experiment 2 involved 86 estrous cycles of 33 jennies, inseminated with semen cryopreserved using BC (n = 43 cycles) or mINRA (n = 43 cycles). Each group included control cycles (BC, n = 10; mINRA, n = 10) and three treatments: SP, frozen-thawed semen re-extended in SP (BC, n = 08; mINRA, n = 08); UL, uterine lavage (UL) 10 h post-AI (BC, n = 11; mINRA, n = 11); and SP+UL, frozen-thawed semen re-extended in SP followed by UL 10 h post-AI (BC, n = 14; mINRA, n = 14). RESULTS: Post-thaw motility was similar between cryopreservation protocols (P > 0.05), but adding SP reduced the motility parameters of cryopreserved semen (P < 0.05). PMAI was higher, and LPO and H2O2 were lower in semen cryopreserved using BC (P < 0.05). Seminal plasma addition did not affect PMAI but reduced LPO and H2O2 (P < 0.05). Pregnancy rates did not differ between semen cryopreserved using BC (21 %) and mINRA (23 %; P > 0.05). The SP+UL-assigned cycles had higher fertility rates (43 %; P = 0.01) compared to control-assigned cycles (0/20), whereas SP- (13 %) and UL-cycles (23 %) had intermediate pregnancy rates (P > 0.05). CONCLUSION: Cryopreservation protocol did not impact sperm quality or fertility. However, the association of semen re-extension in SP and post-insemination UL improved fertility outcomes in jennies.